2011
DOI: 10.1080/09540121.2011.555737
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent premarital sex and health outcomes among Taiwanese youth: perception of best friends' sexual behavior and the contextual effect

Abstract: This study explores premarital sex among adolescents and its health outcomes in a typical East Asian society, Taiwan. As a collective society in terms of cultural heritage, a particular target of this study was perceived peer pressure and its contextual influence. The data were taken from the Taiwan Youth Project, 2004 and 2007, and never married youth aged 20 years constituted our sample (N=3530). Best friends' sexual behavior and other context-related factors, such as school attendance and community particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
4
31
0
Order By: Relevance
“…This belief, whether correct or not, may influence individual behaviour. A positive and significant association between perceived peers' sexual behaviour and the likelihood of adolescent premarital sexual engagement has been shown after adjustment for young people's attitudes, individual characteristics and family background (Chiao and Yib 2011). Peer norms are also considered to be markedly more liberal than wider societal norms.…”
Section: Discussionmentioning
confidence: 98%
“…This belief, whether correct or not, may influence individual behaviour. A positive and significant association between perceived peers' sexual behaviour and the likelihood of adolescent premarital sexual engagement has been shown after adjustment for young people's attitudes, individual characteristics and family background (Chiao and Yib 2011). Peer norms are also considered to be markedly more liberal than wider societal norms.…”
Section: Discussionmentioning
confidence: 98%
“…Second, the TYP data was based on self-reported recall of psychological distress, raising the issue of recall bias. Third, adolescents were asked to provide personal, private information about their sexual activities and may have been somewhat reluctant in that regard despite a previous study (Chiao & Yi, 2011) validating self-reports of sexual activity within the TYP sample. Fourth, attrition in a panel sample is always a concern.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 2851 of the 2888 sampled individuals completed the initial interview. Response rates were 99, 88, 72, 64, and 63% for respective waves (Chiao & Yi, 2011). The sample was restricted to adolescents with complete data on psychological distress and pubertal developmental questions, yielding 2595 adolescents at initial assessment, 2330 in 2001, 1899 in 2003, 1690 in 2005, and 1722 in 2007.…”
Section: Data and Samplementioning
confidence: 99%
“…Factors not well understood, but likely to be of importance in early sexual debut are the social expectations based on gender. Despite varying contextual circumstances, positive or negative perceptions of sexual intercourse appear to influence the onset or delay of sexual intercourse (Chiao, 2011). The aim of the present study was to assess gender differentials in factors influencing sexual initiation among adolescents in Zambia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies, including those assessing adolescent sexual attitudes and longitudinal associations with coital debut, have concluded that adolescents are more likely to initiate sex if they have permissive or positive attitudes towards sex (Whitbeck et al, 1999). Despite varying contextual circumstances, positive or negative perceptions of sexual intercourse appear to influence the onset or delay of sexual intercourse (Chiao, 2011).…”
Section: Introductionmentioning
confidence: 99%